Evidence for herpes simplex viral latency in the human cornea. Issue 4 (April 1991) - Kaye, S B; Lynas, C; Patterson, A; Risk, J M; McCarthy, K; Hart, C A
Abstract : Patients undergoing penetrating keratoplasty for prior herpes simplex keratitis (group A) and corneal disease unrelated to herpes simplex (group B) were investigated to assess whether the cornea is a site for herpes simplex viral latency. All patients were seropositive for herpes simplex viral antibody. Virus was isolated from the tear film postoperatively in one patient and on cocultivation from the cornea of another patient. Herpes simplex viral DNA, however, was detected in the corneas of all patients from group A and half of those from group B by means of the polymerase chain reaction and primers to three well separated regions of the viral genome. Three donor corneas had no evidence of herpes simplex viral DNA. Using RNA polymerase chain reaction, we found evidence of a latency associated transcript and also that of a glycoprotein C coding transcript in two corneas, indicating viral replication. Nine corneas had evidence of a latency associated transcript but no glycoprotein C transcript, which suggests that herpes simplex virus may be maintained in a latent state in the corneas of patients with prior herpes simplex keratitis and in some patients with corneal disease unrelated to the herpes simplex virus.